2018
DOI: 10.1007/s13365-018-0635-3
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia shrinkage without remarkable hippocampal atrophy in chronic aviremic HIV-positive patients

Abstract: Conventional magnetic-resonance (MR) imaging is not sensitive enough in depicting subtle neurodegenerative changes that occur during chronic HIV infection with good peripheral viral suppression. The aim of this study was to compare brain volumes in HIV-positive subjects with age- and education-matched healthy controls with regard to influence of aging and immunologic parameters. An overall of 65 subjects (40 HIV-positive and 25 age-, gender-, and education-matched healthy subjects) underwent conventional MR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Moreover, the bilateral thalamus showed atrophy in preclinical HAND compared with NCs, which is consistent with previous research findings in that the atrophy was also observed in the same region even in the neurocognitively asymptomatic stage ( Tesic et al, 2018 ). For early-infected HIV individuals, the decreased volume in the thalamus may be related to hypometabolism, and hypometabolism in the thalamus was more pronounced than in the whole brain in HIV participants compared with NCs ( Hammoud et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the bilateral thalamus showed atrophy in preclinical HAND compared with NCs, which is consistent with previous research findings in that the atrophy was also observed in the same region even in the neurocognitively asymptomatic stage ( Tesic et al, 2018 ). For early-infected HIV individuals, the decreased volume in the thalamus may be related to hypometabolism, and hypometabolism in the thalamus was more pronounced than in the whole brain in HIV participants compared with NCs ( Hammoud et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Cases 3 and 5 exhibited major subcortical atrophy, consistent with severe HIV-related brain injury. [42][43][44][45] This level of subcortical atrophy potentially biased the measurement of amyloid in the basal ganglia. Nevertheless, there is at least 1 plausible mechanism for the abnormally low level of amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most consistent findings is subcortical atrophy in HIV, even in the era of cART (Becker et al, 2011). Studies have linked atrophy in basal ganglia to neurocognitive impairment (Kumar, Ownby, Waldrop-Valverde, Fernandez, & Kumar, 2011), disrupted cerebral metabolite levels (Cohen et al, 2010;Hua et al, 2013), HIV-disease duration (Ances, Ortega, Vaida, Heaps, & Paul, 2012;Becker et al, 2011), history of immune dysfunction (Tesic et al, 2018), immune recovery (Fennema-Notestine et al, 2013), and viral suppression (Guha et al, 2016;Kallianpur et al, 2013;Krivine et al, 1999). Studies have even suggested that the size of caudate nucleus might serve as a potential biomarker of HAND (Dal Pan et al, 1992;Hestad et al, 1993;Kieburtz et al, 1996).…”
Section: Introductionmentioning
confidence: 99%